2018
DOI: 10.24093/awej/vol9no4.32
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Language Learners’ Attitudes and Perceptions of L1 Use in L2 Classroom

Abstract: Whether to avoid learners' first language (L1) or to make use of it in the second language (L2) classes is a controversial issue. Some studies have challenged the effectiveness of the monolingual approach to foreign language learning. This study investigates Saudi university learners' attitudes and perceptions towards incorporating their L1(Arabic) in English class. This study also sheds light into the relationship between students' perceptions and proficiency level in the target language. To this end, Gaebler… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The findings showed that most female Saudi Arabian EFL students who participated in this study had positive attitudes toward using the MT (Arabic) in English grammar classes. This finding agrees with previous research on EFL students' attitudes toward MT use in EFL classes, indicating that EFL learners hold positive attitudes toward MT use in class (Brooks-Lewis, 2009;Al-Nofaie, 2010;Al-Shammari, 2011;Al-Mohaimeed and Al-Murshed, 2018;Kocaman and Aslan, 2018). However, this finding differs from Nazary's (2008) findings, reporting negative attitudes of the EFL students toward such use.…”
Section: Discussionsupporting
confidence: 91%
“…The findings showed that most female Saudi Arabian EFL students who participated in this study had positive attitudes toward using the MT (Arabic) in English grammar classes. This finding agrees with previous research on EFL students' attitudes toward MT use in EFL classes, indicating that EFL learners hold positive attitudes toward MT use in class (Brooks-Lewis, 2009;Al-Nofaie, 2010;Al-Shammari, 2011;Al-Mohaimeed and Al-Murshed, 2018;Kocaman and Aslan, 2018). However, this finding differs from Nazary's (2008) findings, reporting negative attitudes of the EFL students toward such use.…”
Section: Discussionsupporting
confidence: 91%
“…The use of translation might be helpful at certain early stages of the learning process as some researches as proved through examining the usage of translation on students at different levels -from Grade 10 (Laufer and Girsoi, 2008), Elementary School (Ramachandran and Rahim, 2004; Calis and Dikilitas, 2012), High School (Moritomo and Loewen, 2007) and preparatory courses in university (Almohaimeed and Almurshed, 2018). According to these studies, translation helps students to memorize and overcome learning difficulties as well as enable them to comprehend the target language through their mother tongue.…”
Section: The Use Of Translation As a Learning Strategy (The Argument)mentioning
confidence: 99%
“…Using learners' first language (L1) in the second language (L2) classroom has been an ongoing debate among researchers in L2 teaching. While several researchers acknowledge that the use of L1 within L2 classroom has a limited role on L2 learning progress (Almohaimeed & Almurshed, 2018;Ghobadi & Ghasemi, 2015;Çelik & Aydın, 2018), others believe that its uses support learners in making the most of their L2 learning. Debreli (2016), for instance, contends that the use of L1 in L2 classroom helps learners, in particular, to understand better teachers' explanation on specific difficult topics and new lexical items, while Dewi and Setiadi (2018), as well as Tsagari and Giannikas (2018), believe that use it in a principled way help teachers and learners to foster L2 teaching and learning.…”
Section: Introductionmentioning
confidence: 99%
“…Brown (1994) has argued that the target language system is learned through the process of struggling to communicate. It is on this ground that most opinion on limiting the use of L1 in L2 classroom has been based and suggesting that L2 learners should have meaningful exposure to the L2 to obtain the most benefit (Almohaimeed & Almurshed, 2018;Ghobadi & Ghasemi, 2015;Karimian & Mohammadi, 2015).…”
Section: Introductionmentioning
confidence: 99%